Risk Factors for Adverse Birth Outcomes in the PROMISE 1077BF/1077FF Trial - Sebikari, Dorothy (J Acquir Immune Defic Syndr, 2019)
BACKGROUND: In the multi-country PROMISE 1077BF trial, the risk of low birth weight (LBW; <2500g) and preterm delivery (PTD; <37 weeks) was higher among women initiating a protease inhibitor (PI)-based antiretroviral treatment (ART) regimen than in those receiving ZDV alone. Among those assigned to a PI regimen, tenofovir/emtricitibine was associated with the more severe outcomes of very LBW (VLBW; <1500g) and very PTD (VPTD; <34 weeks) compared to zidovudine/lamivudine. METHODS: We used multivariate logistic regression to further explore treatment findings, taking into account demographic baseline clinical and post-entry obstetrical factors. We evaluated individual adverse outcomes and composites that included stillbirth and early loss/spontaneous abortion. RESULTS: Among 3333 women delivering at least one live infant, median maternal age at enrollment was 26 years; 661 (20%) were primiparous, and 110 (3.3%) reported at least one prior PTD. Seventeen percent of newborns were LBW, 1% were VLBW, 17% had PTD, and 3% VPTD. Treatment allocation remained strongly associated with multiple adverse outcomes after controlling for other risk factors with both ART regimens exhibiting increased risk relative to ZDV alone. Other risk factors remaining significant in at least one of the multivariate models included: country, gestational age at entry, maternal age, maternal BMI, prior PTD, history of alcohol use, baseline HIV viral titer, multiple gestation and several obstetric risk factors. CONCLUSION: ART effects on adverse pregnancy outcomes reported in the randomized PROMISE trial remained strongly significant even after controlling for demographic, baseline clinical and obstetrical risk factors, which were also associated with these outcomes.